Пастирське городище: керамічний комплекс із засипки внутрішнього рову (за результатами досліджень у 2017 р.) - Скиба, А.В.; Баранов, В.І. (Археологія і давня історія України, 2019)
Стаття присвячена керамічному комплексу,
виявленому в шарі засипки одного з внутрішніх
ровів Пастирського городища, на ділянці, що була досліджена у 2017 р. Комплекс кераміки включає
грубо ліпний слов'янський та кружальний посуд пастирського типу. The article is devoted to the ceramic complex from
the inner moat of the Pastyrske hill-fort (plot, investigated
in 2017). At the site fragments are at least 20
ceramic vessels — 16 hand-made vessels and 4 whellmade
vessels. Chronological indicators found on the
object allow to determine the chronological date of creation
of the complex within the middle of the 7th — the
middle of the 8th century.
The nature of the layer in which the ceramics was
found indicates that the ditch was purposefully filled
in a short time after the fire on the territory of the settlement.
This ceramic crockery is most likely to come
from structures located on the territory of the «citadel»
of the settlement and were destroyed during a fire.